Bird communities and vegetation composition in Nusa Penida, Bali, Indonesia - Franciscus Xaverius Sudaryanto; Junita Hardini; Lalu Achmad Tan Tilar Wangsajati Sukmaring Kalih; Muhammad Mirzan Asrori; I Wayan Suana (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Sudaryanto FX, Hardini J, Kalih LATTWS, Asrori MM, Suana IW. 2019. Bird communities and vegetation composition in Nusa Penida, Bali, Indonesia. Biodiversitas 20: 3676-3683. A study on bird community and vegetation composition in Nusa Penida was carried out to determine its diversity, conservation status, and habitat as an effort to conserve and develop birdwatching ecotourism in Nusa Penida. The study was conducted in Tembeling forest and Ped agroforestry. By using the point count method, we found 80 species of birds: 70 species in Tembeling forest and 79 species in Ped agroforestry. Fourteen species of birds are protected by Indonesian law. According to the IUCN Red List of Threatened Species, four species are Critically Endangered and one species is classified as Near Threatened. We also found eight species of migratory birds. Diversity of birds in Nusa Penida was high. Individuals of each bird species was spread evenly, except Hirundo rustica, Hirundo tahitica and Streptopelia chinensis were dominant. Twenty-five species of trees were found in Tembeling, while in Ped were found 22 species. These vegetations were provided birds with good resources for foraging, resting, and nesting.